The Role of Device Fingerprinting, User Behavior, and Shipping Address in Preventing Promotion Abuse in Indonesian E-Commerce Platforms - Eric Fo Candra; Lis Sintha; Denny Tewu (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research investigates the utilization of device data to identify user behaviors associated with promotion abuse on Indonesian e-commerce platforms. Promotion abuse refers to fraudulent activities where individuals exploit promotional systems, often by creating multiple fake accounts or using the same device for claims repeatedly. The purpose of this study is to examine the relationship between device fingerprinting, user behavior patterns, shipping address data, and the effectiveness of fraud prevention systems. Using a quantitative approach, data were collected from fraud reports made between June 2018 and May 2019. Multiple regression was applied to test the proposed hypotheses. The findings show that device fingerprinting, user behavior, and suspicious delivery address variables significantly affect fraud detection effectiveness. This study highlights the importance of integrating behavioral analysis and device-based data into fraud detection systems to proactively minimize promotional abuse. These insights provide practical implications for e-commerce companies looking to improve their digital security measures and maintain consumer trust.